2008
DOI: 10.1091/mbc.e07-07-0666
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Differentiated Quiescent and Nonquiescent Cells in Yeast Stationary-Phase Cultures

Abstract: Cells in glucose-limited Saccharomyces cerevisiae cultures differentiate into quiescent (Q) and nonquiescent (NQ) fractions before entering stationary phase. To understand this differentiation, Q and NQ cells from 101 deletion-mutant strains were tested for viability and reproductive capacity. Eleven mutants that affected one or both phenotypes in Q or NQ fractions were identified. NQ fractions exhibit a high level of petite colonies, and nine mutants affecting this phenotype were identified. Microarray analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
193
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(207 citation statements)
references
References 67 publications
14
193
0
Order By: Relevance
“…We found no requirement for several chromatin factors implicated in expression memory, including the deacetylase SIR2, the Pho23p subunit of the Rpd3-large histone deacetylase complex, or the histone variant H2A.z (Q. Guan and A. P. Gasch, unpublished data). We also found no significant differences in transcript abundance after cells had re-acclimated to stress-free medium, nor evidence of a sequestered pool of nontranslated, stored mRNAs (Aragon et al 2008) (data not shown). These negative results are consistent with the dispensability of nascent protein synthesis in maintaining the memory of H 2 O 2 tolerance.…”
Section: Mechanism Of Cellular Memory Of Stress Resistancementioning
confidence: 71%
“…We found no requirement for several chromatin factors implicated in expression memory, including the deacetylase SIR2, the Pho23p subunit of the Rpd3-large histone deacetylase complex, or the histone variant H2A.z (Q. Guan and A. P. Gasch, unpublished data). We also found no significant differences in transcript abundance after cells had re-acclimated to stress-free medium, nor evidence of a sequestered pool of nontranslated, stored mRNAs (Aragon et al 2008) (data not shown). These negative results are consistent with the dispensability of nascent protein synthesis in maintaining the memory of H 2 O 2 tolerance.…”
Section: Mechanism Of Cellular Memory Of Stress Resistancementioning
confidence: 71%
“…Although potentially interesting, it is not yet clear why only half of the cells in these stationary-phase cultures appear to be able to form cytoplasmic granules. One interesting possibility is suggested by previous work indicating that only 50% of the cells in stationary-phase cultures exhibit the ability to remain viable for long periods of time (Allen et al 2006;Aragon et al 2008). These cells have been termed the Q, or quiescent, fraction of this population and may correspond to those cells that have a focus in our studies here.…”
Section: Resultsmentioning
confidence: 92%
“…This suggests that biological heterogeneity is still somehow triggered by genetic heterogeneity. This is also supported by the fact that Aragon et al (2008) identified mutations affecting reproductive capacity and/or viability.…”
Section: Discussionmentioning
confidence: 73%
“…Weinberger et al (2007) showed that yeast cells more efficiently able to arrest in G1 phase when entering into stationary phase exhibited longer chronological lifespans than cells arrested in S phase. The study of gene expression in quiescent and nonquiescent cells (Aragon et al, 2008) showed that nonquiescent cells seemed unable to arrest growth. In contrast, quiescent cells exhibited gene expression showing they had the capacity to survive prolonged starvation and to respond quickly if conditions became favorable to growth.…”
Section: Discussionmentioning
confidence: 99%